Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.ymthe.2018.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant BCG Overexpressing phoP-phoR Confers Enhanced Protection against Tuberculosis

Abstract: The live tuberculosis vaccine Mycobacterium bovis BCG (Bacille Calmette-Guérin) comprises a number of genetically distinct substrains. In BCG-Prague, phoP of the PhoP-PhoR two-component system is a pseudogene due to a single insertion mutation. We hypothesized that this mutation partially accounts for the low immunogenicity of BCG-Prague observed in the 1970s. In this study, we showed that complementation with the M. bovis allele of phoP restored BCG-Prague’s immunogenicity. Furthermore, we showed that overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 83 publications
(139 reference statements)
0
10
0
Order By: Relevance
“…Guinea pigs subcutaneously vaccinated with rBCG-Japan had a reduced bacterial load after 8 weeks compared to unvaccinated guinea pigs (lung p < 0.05; spleen n.s.) and increased survival by 133% over the parental BCG strain after M. tb H37Rv infection [35]. This study suggested that recombinant BCG overexpressing phoP-phoR is a promising candidate to replace BCG.…”
Section: Rbcgs Modulating Immunogenicitymentioning
confidence: 69%
See 2 more Smart Citations
“…Guinea pigs subcutaneously vaccinated with rBCG-Japan had a reduced bacterial load after 8 weeks compared to unvaccinated guinea pigs (lung p < 0.05; spleen n.s.) and increased survival by 133% over the parental BCG strain after M. tb H37Rv infection [35]. This study suggested that recombinant BCG overexpressing phoP-phoR is a promising candidate to replace BCG.…”
Section: Rbcgs Modulating Immunogenicitymentioning
confidence: 69%
“…A major hindrance is the lack of a known immune correlate of protection in animals and humans [116]. As evidenced by many clinical and preclinical studies, robust immunogenicity does not always translate to improved protective efficacy [26,35,102]. Another hurdle is the lack of an animal model that faithfully recapitulates the spectrum of human TB disease including latent TB infection (LTBI) [117].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 4) Another refinement to the use of RD1 was recently reported in the BCG::ESAT6-PE25SS strain, which secretes full-length ESAT-6 via the ESX-5 secretion system, and reduced M. tuberculosis H37Rv loads in lungs as well lung pathology in intratracheallyvaccinated C57BL/6 more than parental BCG [52], so it will be interesting to see further development of this vaccine candidate. (5) BCG::phoPR, an interesting candidate based on the fact that the phoPR genes from BCG Pasteur were introduced into BCG Japan to restore it from its natural point mutations, and which prolonged survival of guinea pigs infected with M. tuberculosis H37Rv compared with parental BCG [53]. Whether this specific recombinant BCG strain will undergo further development or will be the basis of possible restoration of gene function in other rBCG vaccine candidates remains to be seen.…”
Section: Novel Live Attenuated Bcg-based Vaccine Candidates: What Has Been Shown and What Is Still Missing?mentioning
confidence: 99%
“…Speaking of the genetic characteristics of BCG strains, it is interesting to consider one of them in more detail. In research on the BCG-Prague strain, a phoP gene mutation was detected in the form of a single nucleotide insert, which led to the destruction of the C-terminal DNA-binding domain [ 11 , 12 ]. This mutation is specific for BCG-Prague and is not found in other BCG strains [ 13 ].…”
Section: Introductionmentioning
confidence: 99%